Computational analysis and experimental evidence of two typical levelers for acid copper electroplating. (20th May 2018) - Lai, Zhiqiang; Wang, Shouxu; Wang, Chong; Hong, Yan; Chen, Yuanming; Zhang, Huaiwu; Zhou, Guoyun; He, Wei; Ai, Kehua; Peng, Yongqiang
Abstract: In this work, the leveling effect of two typical levelers for copper electroplating, Janus Green B (JGB) and polymerizates of imidazole and epichlorohydrin (IMEP) are both analyzed through computational calculations and electrochemical experiments. Frontier Molecule Orbital (FMO) and the electrostatic potential (ESP) of JGB, IMEP and accelerated complex MPS-Cu(I) are calculated and visualized by Density Functional Theory (DFT) method to predict the preferable reaction sites for electrophilic or nucleophilic attack and the corresponding interactions. The adsorption processes of JGB and IMEP with MPS-Cu(I) on copper surface are examined through molecular dynamics (MD) simulation. According to the results of calculations, we conclude that IMEP is the better candidate for electroplating at high current density in comparison with JGB. The results from electrochemical tests validate that MPS has both synergistic and antagonistic effect with IMEP and has an antagonistic effect with JGB. Electroplating tests confirms that the system with IMEP exhibits a better leveling effect at higher current density. In addition, relatively higher ESP value is preferred for a leveler in a large current density electroplating.